Innovative solutions for building community in academic libraries - Bonnand, Sheila; Hansen, Mary Anne 1961- (Advances in library and information science (ALIS) book series, 2015)
The library has always been an essential part of the collegiate experience, providing students with access to knowledge and literature. However, as virtual services and online learning become more prominent within collegiate environments, the ways students conduct research and access resources has been altered. Innovative Solutions for Building Community in Academic Libraries examines new methods librarians use to engage both on-campus and online users in library services, taking into account the significant impacts of online learning on students interaction with library resources. Focusing on various outreach practices, techniques of literacy instruction, and the utilization of library spaces, this research-supported book is a pivotal reference source for distance educators, program planners, academics, and library professionals interested in new ways to attract users to library services.--Provided by publisher.